Salmonellosis as risk factor for stillbirth in guinea pigs - Ortega O., Gabriela (2015)
The association between positive cases of Salmonella sp isolated from vaginal swabs collected within 24 hours of the parturition and stillbirth in a guinea pig farm in Huancayo, Peru was evaluated. The study included 258 breeding females using a CaseControl design, where litter size was paired between the two groups and parity and number of birth and barn of the breeding female were used as co-variables. In the ‘Case’ group were included females with at least one stillbirth per litter and in the ‘Control’ group were included females where the entire litter was alive. Results showed that 8.5% of the breeding females in the ‘Case’ group were positive to Salmonella sp, and by the logistic regression analysis was estimated an Odds Ratio of 4.32 (95% confidence interval; p<0.05) for positive cases in relation to the controls. On the other hand, the cause of death in 91.5% (118/129) of the females with stillbirths was due to other infectious or noninfectious causes. The results show that Salmonella should be considered as a cause of stillbirths in guinea pigs.